Koi Fish Pond, Seth Samaldas Narsidas pyaav - Ghosh, Ayan (2023)
Though it is known that Seth Samaldas Narsidas pyaav was erected in 1903, it is not known where it was originally located before it was installed at Jijamata Udyan. The pyaav was in derelict condition before it was restored by the Heritage Cell of Brihanmumbai Municipal Corporation. The fountain was converted into a Koi Fish Pond on the site of an existing well.